Analysis of Strengthening Land Administration Data for Strategic Development Projects - Sabina Adilla (Faculty of Law, Universitas Negeri Semarang, 2025)
This study examines legal uncertainty in land management for the Jragung Dam project in Semarang Regency, which is part of a national strategic project. Land conflicts in this project are triggered by overlapping land ownership claims, lack of inter-agency coordination, and limited transparency in the land acquisition process. The resulting legal uncertainty not only affects the impacted communities but also hinders the smooth implementation of the project. This study aims to analyze the factors causing legal uncertainty and to identify applicable solutions to minimize land conflicts. The approach used is a normative-empirical legal method with a descriptive analysis. Primary data were collected through interviews with the community in Dusun Kedungglatik, the National Land Agency (BPN), and the Ministry of Environment and Forestry (KLHK), while secondary data were obtained from official documents and relevant literature.The findings indicate that the utilization of Geographic Information System (GIS) technology and drone-based mapping can enhance the accuracy of land data and reduce potential conflicts arising from land registration errors. Additionally, improving inter-agency coordination, actively involving communities in decision-making, and providing a more effective dispute resolution mechanism are the main recommended solutions. More adaptive regulations concerning spatial planning changes and forest boundary adjustments are also needed to prevent harm to local communities. With a more transparent and accurate land administration system, similar conflicts can be prevented in the future to the development of a fairer and more sustainable land policy while supporting the smooth progress of national strategic projects without neglecting the rights of affected communities.